Bridging theory and practice in peer-to-peer energy trading: market mechanisms and technological innovations - Pravesh Raghoo; Kalim Shah (Environmental Research: Infrastructure and Sustainability)
The article provides a synthesis of the literature on the peer-to-peer (P2P) energy trading paradigm. P2P energy trading is a prosumer business model and a transformative concept that allows prosumers to sell surplus generation to other prosumers and consumers within an energy community or microgrid. P2P energy trading is a novel concept to promote decentralization, decarbonization, democratization, digitalization, and enhancing energy resilience of the energy sector. The article covers different facets of P2P energy trading, including market designs, changing actor roles, pricing mechanisms, enabling technologies, and challenges. The article thus addresses emerging and complementary aspects not covered in prior literature reviews. As such, three market designs are discussed: centralized, decentralized, and distributed, and four pricing mechanisms, which are optimization, game theory, auction-based, and reinforcement learning. Enabling technologies discussed are Energy Internet, Internet of Things, Artificial intelligence, Blockchain, Communication networks, and battery flexibility. The paper discusses the challenges that the development and commercialization of the P2P energy trading faces—especially focusing on the social ontology of the concept—and provides research directions to amplify the scaling up of the technology.